Progress in biomaterials
"Progress in Biomaterials is a multidisciplinary, English-language publication of original contributions and reviews concerning studies of the preparation, performance and evaluation of biomaterials; the chemical, physical, biological and mechanical behavior of materials both in vitro and in vivo in areas such as tissue engineering and regenerative medicine, drug delivery and implants where biomaterials play a significant role."